2023
DOI: 10.29333/mathsciteacher/12622
|View full text |Cite
|
Sign up to set email alerts
|

Mediation and moderation effect of mathematics interest and teaching quality between self-concept and mathematics achievement

Abstract: <b>Purpose: </b>This study investigated the mediation and moderation effect of mathematics interest and teaching quality on the relationship between self-concept and mathematics achievement.<br /> <b>Design/methodology/approach</b>: The study was conducted at Sakafia Islamic Senior High School (SHS) and Kumasi Academy SHS in Ghana. A sample comprised of 300 students who offered general arts, general science, and home economics were randomly selected from a population of 1,200. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…A study by Boadu et al (2023) found that math achievement of children is significantly predicted by the quality of the teacher. Similar findings were made by Fosu et al (2022) who examined Sakafia Islamic Senior High School (SHS) and Kumasi Academy Senior High School (SHS) with a sample size of 300 students. They discovered that teacher quality had a favorable but small impact on students' achievement in mathematics.…”
Section: The Effect Of Teacher Quality On Mathematics Achievementsupporting
confidence: 71%
“…A study by Boadu et al (2023) found that math achievement of children is significantly predicted by the quality of the teacher. Similar findings were made by Fosu et al (2022) who examined Sakafia Islamic Senior High School (SHS) and Kumasi Academy Senior High School (SHS) with a sample size of 300 students. They discovered that teacher quality had a favorable but small impact on students' achievement in mathematics.…”
Section: The Effect Of Teacher Quality On Mathematics Achievementsupporting
confidence: 71%
“…Teachers' practical knowledge is developed through participating in and reflecting on action and experience and is dependent on the specific context in which it is materialized (Elbaz, 2018;Segal et al, 2021;Steele & Rogers, 2012;Van Driel, 2021). Finally it is all about the teachers and students perceiving capacity of learning mathematics, who are responsible for the development of the subject (Fosu et al, 2023;Park et al, 2017).…”
Section: Introductionmentioning
confidence: 99%